Genome sequencing and population genomics modeling provide insights into the local adaptation of weeping forsythia. (1st August 2020) - Li, Lin-Feng; Cushman, Samuel A; He, Yan-Xia; Li, Yong
Abstract: Understanding the genetic basis underlying the local adaptation of nonmodel species is a fundamental goal in evolutionary biology. In this study, we explored the genetic mechanisms of the local adaptation of Forsythia suspensa using genome sequence and population genomics data obtained from specific-locus amplified fragment sequencing. We assembled a high-quality reference genome of weeping forsythia (Scaffold N50 = 7.3 Mb) using ultralong Nanopore reads. Then, genome-wide comparative analysis was performed for 15 natural populations of weeping forsythia across its current distribution range. Our results revealed that candidate genes associated with local adaptation are functionally correlated with solar radiation, temperature and water variables across heterogeneous environmental scenarios. In particular, solar radiation during the period of fruit development and seed drying after ripening, cold, and drought significantly contributed to the adaptive differentiation of F. suspensa . Natural selection exerted by environmental factors contributed substantially to the population genetic structure of F. suspensa . Our results supported the hypothesis that adaptive differentiation should be highly pronounced in the genes involved in signal crosstalk between different environmental variables. Our population genomics study of F. suspensa provides insights into the fundamental genetic mechanisms of the local adaptation of plant species to climatic gradients.